Faktor-faktor yang Mempengaruhi Tingkat Pengangguran Terbuka di Eks Karesidenan Surakarta Periode 2017-2021 - Bagas Rejatama Waluyaning Putra; Sitti Retno Faridatussalam (Universitas Batanghari Jambi, 2023)
Unemployment is an employment problem that is aften faced by every country, especially developing countries such as Indonesia, This study aims to analyze and find out how much influence the human development index, job opportunities, and the number of poor people have on the open unemployment rate in the former Surakarta Residency in 2017-2021. The sample of this research was conducted in 7 regencies/citites in the former Surakarta Residency. This type of research is quantitative research, and used secondary data obtained from the Central Statistics Agency (BPS). The data analysis method used is panel data regression which combines time series data and cross section data. The best model in this study is the Random Effect Model (REM). Based on the results of data analysis shows that all variables, namely the human development index, job opportunities, and the number of poor people have a significant effect on the open unemployment rate.